The historical development of Końskowola - Niedźwiadek, Rafał (Institute of Archaeology Rzeszów University, 2012)
Końskowola was granted a town charter in the early 16th century. The town was founded by Andrzej Tęczyński. Archaeological and historical sources imply that permanent settlement in that area began already in the early Middle Ages. At first parish was founded and then management center for nobles goods was established. The creation of the city was the culmination of this process.
Kształtowanie przestrzeni miejskiej w Końskowoli
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology, medieval; parish centre; settlement; city archaeology; Tenczyński family; Końskowola